Thermally conductive sheet, method for manufacturing thermally conductive sheet, heat dissipating component and semiconductor device
By covering the carbon fiber of the adhesive resin and the insulating film on the heat conducting sheet and removing the insulating film when contacting, the problems of short circuit and thermal conductivity of the heat conducting sheet are solved, and efficient electrical insulation and thermal conductivity are achieved.
Patent Information
- Application Number
- CN202010647909.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-10-09
- Filing Date
- 2015-10-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2035-10-27
AI Technical Summary
When the existing heat conductor sheet comes into contact with the semiconductor element circuit, the short circuit risk is caused by defects in the conductive filler, and in order to ensure electrical insulation, the high thermal conductivity effect of the thermal conductivity is damaged.
The sheet body cured with a thermally conductive resin composition is covered with carbon fibers of adhesive resin and insulating film. It is covered by uncured components of the slice and adhesive resin to remove the insulating film and ensure electrical insulation and high thermal conductivity. Rate.
It is achieved to prevent short circuits in unexpected situations such as contact, maintain high thermal conductivity, reduce thermal resistance, and improve the insulation and mechanical properties of the thermal conductor.
Smart Images

Figure CN111739856B_ABST
Abstract
Description
[0001] This application is a divisional application of the original application, with the application date of October 27, 2015, the application number 201580055236.8, and the invention name of "Heat conductive sheet, method for manufacturing heat conductive sheet, heat dissipation component and semiconductor device". Technical Field
[0002] The present invention relates to a heat conducting sheet arranged between a heat generating body such as a semiconductor element and a heat dissipating body such as a heat sink, a method for manufacturing the heat conducting sheet, a heat dissipating component having the heat conducting sheet, and a semiconductor device. Background Art
[0003] Conventionally, semiconductor elements mounted on various electrical devices such as personal computers and other devices generate heat due to driving. If the generated heat is accumulated, it will have an adverse effect on the driving of the semiconductor element and peripheral devices, so various cooling means are used. As cooling methods for electronic components such as semiconductor elements, there are known methods of installing a fan on the device and cooling the air in the device frame, and installing a heat dissipation fan, a heat dissipation plate or other heat sink on the semiconductor element to be cooled.
[0004] When a semiconductor element is mounted on a heat sink for cooling, a heat conductive sheet is provided between the semiconductor element and the heat sink in order to efficiently release the heat of the semiconductor element. As the heat conductive sheet, a heat conductive sheet containing a heat conductive filler (e.g., flaky particles (boron nitride (BN), graphite, etc.), carbon fiber, etc.) dispersed in a silicone resin is widely used (see Patent Document 1).
[0005] It is known that these thermally conductive fillers have thermal anisotropy. For example, when carbon fiber is used as a thermally conductive filler, the thermal conductivity in the fiber direction is about 600 W / m·K to 1200 W / m·K. When boron nitride is used, the thermal conductivity in the surface direction is about 110 W / m·K and the thermal conductivity in the direction perpendicular to the surface direction is about 2 W / m·K, which is anisotropic.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-23335 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, in the case of a thermally conductive sheet using a thermally conductive filler such as carbon fiber which has excellent thermal conductivity and also electrical conductivity, when the thermally conductive sheet comes into contact with a circuit around a semiconductor element, or a defect occurs in the sheet and falls onto the circuit, there is a concern that the thermally conductive filler exposed from the surface of the sheet may cause a short circuit or other failure of the electronic device.
[0011] On the other hand, if a thermally conductive filler is buried in the sheet body in order to ensure the electrical insulation of the thermally conductive sheet, the effect of high thermal conductivity provided by the thermally conductive filler is impaired.
[0012] Here, an object of the present invention is to provide a thermally conductive sheet, a method for manufacturing the thermally conductive sheet, a heat dissipating component, and a semiconductor device that can ensure electrical insulation and maintain high thermal conductivity even in unexpected situations such as contact of the thermally conductive sheet.
[0013] Solution to the problem
[0014] In order to solve the above problems, the thermally conductive sheet according to the present invention has a sheet body formed by curing a thermally conductive resin composition, wherein the thermally conductive resin composition contains a binder resin and carbon fibers covered with an insulating film.
[0015] The carbon fibers exposed from the surface of the sheet body are not covered with the insulating film but are covered with a component of the binder resin.
[0016] In addition, the method for manufacturing the thermally conductive sheet according to the present invention comprises the following steps:
[0017] A step of molding a thermally conductive resin composition containing a binder resin and carbon fibers covered with an insulating film into a predetermined shape and curing the resultant to obtain a molded body of the thermally conductive resin composition;
[0018] The step of cutting the molded body into sheets to obtain a sheet body; and
[0019] a step of coating the carbon fibers exposed from the surface of the sheet body with the binder resin component;
[0020] In the step of obtaining the sheet body, the insulating film covering the carbon fibers exposed from the surface of the sheet body is removed.
[0021] Furthermore, the heat dissipating component according to the present invention includes a heat spreader for dissipating heat generated by an electronic component, and the heat conductive sheet disposed on the heat spreader and sandwiched between the heat spreader and the electronic component.
[0022] Furthermore, the semiconductor device according to the present invention includes a heat spreader for dissipating heat generated by the semiconductor element, and the heat conductive sheet disposed on the heat spreader and sandwiched between the heat spreader and the semiconductor element.
[0023] Effects of the Invention
[0024] According to the present invention, since the carbon fibers exposed from the surface of the sheet body are not covered by the insulating film, the decrease in thermal conductivity due to the insulating film can be suppressed. In addition, in the thermally conductive sheet according to the present invention, the carbon fibers exposed from the surface of the sheet body and not covered by the insulating film are covered with a component of the binder resin, so that both the insulation and thermal conductivity of the sheet can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a cross-sectional view showing a heat conductive sheet, a heat dissipating member, and a semiconductor device to which the present invention is applied.
[0026] Figure 2 This is a perspective view showing the process of slicing a resin molded body to cut out a sheet body.
[0027] Figure 3A This is a perspective view showing a sheet body cut out from a resin molded body.
[0028] Figure 3B This is a perspective view showing a state where the sheet body is covered with a binder resin component.
[0029] Figure 4 This is a perspective view showing carbon fibers covered with an insulating film.
[0030] Figure 5 This is a cross-sectional view showing an example of the surface shape of the thermally conductive sheet.
[0031] Figure 6 This is a cross-sectional view showing another example of the surface shape of the thermally conductive sheet.
[0032] Figure 7 This is a perspective view showing a state where the sheet body is pressed via a spacer. DETAILED DESCRIPTION
[0033] Hereinafter, a thermally conductive sheet, a method for manufacturing a thermally conductive sheet, a heat dissipating component, and a semiconductor device to which the present invention is applied will be described with reference to the attached drawings. Figure 1 It is to be noted that the present invention is not limited to the following embodiments, and various changes can be made without departing from the gist of the present invention. In addition, the drawings are schematic, and the ratios of the various dimensions are sometimes different from the actual ones. The specific dimensions should be judged with reference to the following description. In addition, of course, the relationship between the dimensions and the parts with different ratios between the drawings are also included.
[0034] The heat conductive sheet 1 of the present invention is used to dissipate the heat generated by electronic components 3 such as semiconductor elements. Figure 1 As shown, the main surface 2a fixed to the heat spreader 2 facing the electronic component 3 is sandwiched between the electronic component 3 and the heat spreader 2. In addition, the thermally conductive sheet is sandwiched between the heat spreader 2 and the heat sink 5. The thermally conductive sheet and the heat spreader 2 together constitute a heat dissipating member 4 for dissipating heat from the electronic component 3.
[0035] The heat spreader 2 is formed in a square plate shape, for example, and has a main surface 2a facing the electronic component 3 and a side wall 2b provided upright along the outer periphery of the main surface 2a. The heat spreader 2 is provided with a heat conductive sheet 1 on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 is provided on the other surface 2c opposite to the main surface 2a via the heat conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance, and the more effectively the heat of the electronic component 4 such as the semiconductor element is absorbed, so it can be formed using, for example, copper or aluminum with good thermal conductivity.
[0036] Electronic component 3 is a semiconductor element such as BGA, and is mounted on wiring board 6. Heat spreader 2 is also mounted on wiring board 6 at the front end surface of side wall 2b, thereby surrounding electronic component 3 at a predetermined distance by side wall 2b.
[0037] Furthermore, by bonding the heat conductive sheet 1 to the main surface 2a of the heat spreader 2, a heat dissipating member 4 is formed that absorbs the heat generated by the semiconductor element and dissipates the heat through the heat sink 5. The heat spreader 2 and the heat conductive sheet 1 can be bonded together using the adhesive force of the heat conductive sheet 1 itself as described later, but an adhesive can also be used as appropriate. As the adhesive, a known heat dissipating resin or a heat dissipating adhesive film that is responsible for bonding and heat conduction of the heat conductive sheet 1 to the heat spreader 2 can be used.
[0038] [Thermal conductive sheet]
[0039] The thermally conductive sheet 1 has a sheet body 7 formed by curing a thermally conductive resin composition, the thermally conductive resin composition contains an adhesive resin and carbon fibers 11 covered with an insulating film, the carbon fibers 11 exposed from the surface of the sheet body 7 are not covered by the insulating film, and are covered by uncured components 8 of the adhesive resin that seeped out from the sheet body 7.
[0040] like Figure 2 , Figure 3A and Figure 3BAs shown, the thermally conductive sheet 1 is manufactured as follows: a resin molded body 9 formed by curing a thermally conductive resin composition containing a binder resin and carbon fibers 11 covered with an insulating film is cut into a sheet to obtain a sheet body 7 with the carbon fibers 11 exposed on the sheet surface, and then the sheet body 7 is pressed or placed to cover the sheet body 7 and the carbon fibers 11 exposed from the surface of the sheet body 7 with uncured components 8 of the binder resin. It is to be noted that the carbon fibers 11 exposed from the surface of the sheet body 7 are not covered with the insulating film 12. Details will be described later.
[0041] The carbon fibers 11 constituting the thermally conductive sheet 1 are materials for conducting heat from the electronic components 3 to the heat spreader 2 with good efficiency. Regarding the carbon fibers 11, if the average diameter is too small, there is a concern that the specific surface area becomes too large and the viscosity of the resin composition when the thermally conductive sheet 1 is made becomes too high. If the average diameter is too large, there is a concern that the preparation of the molded body becomes difficult. Therefore, the average diameter of the carbon fibers 11 is preferably 5 μm to 12 μm. In addition, the average fiber length is preferably 30 μm to 300 μm. When the average fiber length of the carbon fibers 11 is less than 30 μm, there is a tendency that the specific surface area becomes too large and the viscosity of the thermally conductive resin composition becomes too high. If it is greater than 300 μm, there is a tendency to hinder the compression of the thermally conductive sheet 1.
[0042] The carbon fiber 11 is selected according to the mechanical properties, thermal properties, electrical properties and other characteristics required for the thermal conductive sheet 1. Among them, pitch-based carbon fibers or carbon fibers obtained by graphitizing polybenzazole are preferably used from the aspects of high elastic modulus, good thermal conductivity, high electrical conductivity, electromagnetic wave shielding, low thermal expansion and the like.
[0043] If the content of carbon fibers 11 in the thermally conductive sheet 1 is too small, the thermal conductivity tends to be low, and if it is too large, the viscosity tends to be high, so it is preferably 16% to 40% by volume.
[0044] [Insulation film]
[0045] like Figure 4 As shown, the surface of the carbon fiber 11 is coated with an insulating film 12. The insulating film 12 can be made of a material having excellent electrical insulation, such as silicon oxide, boron nitride, etc. In addition, as a method of coating the carbon fiber 11 with the insulating film 12, for example, a sol-gel method, a liquid phase deposition method, a polysiloxane method, etc. can be cited. In order to improve the adhesion between the carbon fiber 11 and the insulating film 12, the surface of the carbon fiber 11 can be oxidized by a gas phase method, a liquid treatment method, an electrolytic method, etc.
[0046] When the insulating film 12 covering the carbon fibers 11 is made of silicon oxide, the average thickness of the insulating film 12 observed by cross-sectional TEM observation is preferably set to 50 nm or more and less than 100 nm.
[0047] If the insulating film 12 with an average thickness of less than 50 nm is to be formed, the film treatment concentration needs to be reduced, so the film formation takes a long time, productivity is impaired, and the asphalt treatment amount is reduced and waste liquid increases. In addition, even if the film treatment concentration is increased, thickness control is difficult, productivity is impaired, and there is a concern that a portion of the carbon fiber 11 is exposed, and the insulation performance is impaired.
[0048] Furthermore, when the insulating film 12 having an average thickness of 100 nm or more is formed, in addition to the silica that contributes to the formation of the insulating film 12 covering the carbon fiber 11, particulate silica is also formed. Therefore, if the carbon fiber 11 covered with the insulating film 12 is mixed with the binder resin, particulate silica is also mixed at the same time, resulting in deterioration of the thermal resistance value. In addition, a method of adjusting the film thickness by adjusting the film treatment concentration and repeating it multiple times is also considered, but increasing the number of coating treatments will lead to a decrease in production efficiency and an increase in the amount of waste liquid, so it is not preferred.
[0049] [Thermal conductive filler]
[0050] In addition to the carbon fibers 11, a thermally conductive filler such as a fibrous filler, a plate-like filler, a flaky filler, or a spherical filler may be used in combination within a range not impairing the effects of the present invention.
[0051] As thermally conductive fillers, various fillers can be listed, such as metals (e.g., nickel, iron, etc.), glass, ceramics [e.g., oxides (e.g., alumina, silica, etc.), nitrides (e.g., boron nitride, aluminum nitride, etc.), borides (e.g., aluminum boride, etc.), carbides (e.g., silicon carbide, etc.) and other non-metallic inorganic fibers].
[0052] In particular, from the viewpoint of suppressing secondary aggregation of carbon fibers 11 in the thermally conductive resin composition, it is preferred to use 50 to 900 parts by mass of spherical fillers (preferably spherical alumina or spherical aluminum nitride) having a diameter of 0.1 μm to 10 μm relative to 100 parts by mass of carbon fibers 11.
[0053] [Binder resin]
[0054] The binder resin is a substance that holds the carbon fibers 11 and the appropriately added thermally conductive filler in the thermally conductive sheet 1, and is selected based on the mechanical strength, heat resistance, electrical properties, etc. required of the thermally conductive sheet 1. Such a binder resin can be selected from thermoplastic resins, thermoplastic elastomers, and thermosetting resins.
[0055] Examples of the thermoplastic resin include polyethylene, polypropylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl acetal, fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polystyrene, polyacrylonitrile, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymer (ABS) resins, polyphenylene-ether copolymer (PPE) resins, modified PPE resins, aliphatic polyamides, aromatic polyamides, polyimides, polyamide-imides, polymethacrylic acid, polymethacrylates such as polymethyl methacrylate, polyacrylic acids, polycarbonates, polyphenylene sulfide, polysulfones, polyethersulfones, polyether nitrile, polyether ketones, polyketones, liquid crystal polymers, silicone resins, ionomers, and the like.
[0056] Examples of the thermoplastic elastomer include styrene-butadiene block copolymers or hydrogenated products thereof, styrene-isoprene block copolymers or hydrogenated products thereof, styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, vinyl chloride-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, and polyamide-based thermoplastic elastomers.
[0057] Examples of the thermosetting resin include crosslinked rubber, epoxy resin, phenolic resin, polyimide resin, unsaturated polyester resin, diallyl phthalate resin, etc. Specific examples of the crosslinked rubber include natural rubber, acrylic rubber, butadiene rubber, isoprene rubber, styrene-butadiene copolymer rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene copolymer rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butyl rubber, halogenated butyl rubber, fluororubber, urethane rubber, and silicone rubber.
[0058] The thermally conductive resin composition can be prepared by uniformly mixing various additives and a volatile solvent in addition to the fibrous filler and the binder resin as needed by a known method.
[0059] As described later, such a thermally conductive sheet 1 is manufactured as follows: a resin molded body 9 formed by curing a thermally conductive resin composition containing carbon fibers 11 covered with an insulating film 12 in a binder resin is sliced into sheets to obtain a sheet body 7 in which the carbon fibers 11 are exposed from the sheet surface, and then the sheet body 7 is pressed or placed to thereby manufacture the sheet.
[0060] At this time, since the insulating film 12 of the carbon fibers 11 exposed from the sheet surface is removed by slicing, the thermally conductive sheet 1 can suppress a decrease in thermal conductivity due to the insulating film 12. Then, with respect to the thermally conductive sheet 1, by pressing or placing the sheet body 7, the carbon fibers 11 from which the insulating film 12 has been removed are coated with the uncured components 8 of the binder resin that seeped out from the surface, so that both the insulation property and the thermal conductivity of the sheet can be achieved.
[0061] Furthermore, when the thermally conductive sheet 1 is pressed or placed, uncured components 8 of the binder resin ooze out from the sheet body 7 to the entire surface, and the following (1) and (2) are covered with the uncured components 8 .
[0062] (1) Surface of sheet body 7
[0063] (2) The carbon fibers 11 exposed from the surface of the sheet body 7
[0064] Thus, the thermally conductive sheet 1 exhibits slight tackiness (adhesiveness) on the sheet surface. Therefore, the thermally conductive sheet 1 can improve the conformability and adhesion to the surfaces of the electronic component 3 and the heat spreader 2, and can also reduce the thermal resistance in the low load region.
[0065] In addition, the surface of the thermally conductive sheet 1 is coated with the uncured component 8 of the adhesive resin, and the surface exhibits slight adhesiveness, so that it can be bonded to the main surface 2a of the heat spreader 2 or temporarily fixed to the upper surface 3a of the electronic component 3. Therefore, the thermally conductive sheet 1 does not need to use an additional adhesive, and can achieve labor-saving and cost-reduction in the manufacturing process.
[0066] It should be noted that the coating of the surface of the sheet body 7 with the uncured component 8 and the coating of the carbon fibers 11 from which the insulating film 12 has been removed with the uncured component 8 do not necessarily require a thickness that completely buries the carbon fibers 11 from which the insulating film 12 has been removed. As long as the surface of the sheet body 7 and the carbon fibers 11 from which the insulating film 12 has been removed are coated, the thickness may be a degree that allows the shape of the carbon fibers 11 from which the insulating film 12 has been removed to be determined.
[0067] Here, the thermally conductive sheet 1 can obtain the desired slight adhesiveness (adhesiveness) by adjusting the component ratio of the main agent and the curing agent of the binder resin of the thermally conductive resin composition. For example, when a two-component addition reaction type liquid silicone resin is used as the binder resin of the thermally conductive resin composition, the component ratio of the main agent and the curing agent is preferably set to main agent: curing agent = 50:50 to 65:35 (mass ratio).
[0068] By adjusting this component ratio, thermally conductive sheet 1 can maintain its sheet shape, and uncured component 8 of the binder resin can ooze out by pressing or leaving to cover the entire surface of sheet body 7, thereby obtaining moderate slight adhesiveness over the entire sheet.
[0069] On the other hand, if the main agent component is less than the above ratio, the adhesive resin is cured, the thermally conductive sheet 1 lacks flexibility, and the sheet body 7 is not sufficiently covered with the uncured component 8 of the adhesive resin, and at least a portion of the sheet body 7 does not exhibit slight adhesiveness. In addition, if the curing agent component is less than the above ratio, the adhesiveness is excessively exhibited, the sheet shape cannot be maintained, and it becomes difficult to cut out the sheet from the molded body, and the handling property is impaired.
[0070] In addition, the Shore OO hardness of the thermally conductive sheet 1 measured by the ASTM-D2240 method is preferably 70 or less. If the Shore OO hardness of the thermally conductive sheet 1 exceeds 70, the sheet body 7 cannot exhibit sufficient flexibility, and there is a concern that the compliance and adhesion to the surface of the electronic component 3 and the heat spreader 2 will decrease, and the thermal resistance will increase. In addition, the lower limit of the hardness of the thermally conductive sheet 1 is not particularly limited.
[0071] It should be noted that the volume resistivity of the thermally conductive sheet 1 is preferably 1×10 6 Therefore, even if the thermally conductive sheet 1 contacts surrounding circuit components, there is no risk of causing a malfunction of the electronic device.
[0072] The surface shape of the thermally conductive sheet can be exemplified as follows.
[0073] One is as Figure 5 The surface shown is a smooth pattern. In this case, the surface of the uncured component 8 coated with the carbon fibers 11 is smooth.
[0074] Another is as Figure 6 The surface shown has a pattern of convex portions derived from the carbon fibers 11 exposed from the surface of the sheet body 7. In this case, the surface of the uncured component 8 covering the carbon fibers 11 is not smooth, but has convex portions derived from the carbon fibers 11.
[0075] To explain, Figure 5 and Figure 6 In FIG. 1 , the insulating film 12 covering the carbon fibers 11 is omitted.
[0076] [Thermal Conductive Sheet Manufacturing Process]
[0077] The thermally conductive sheet 1 of the present invention can be produced by a production method having the following steps (A) to (D). Each step will be described in detail below.
[0078] <Process A>
[0079] First, the carbon fibers 11 covered with the insulating film 12 and a thermally conductive filler appropriately added are dispersed in a binder resin to prepare a thermally conductive resin composition for forming the thermally conductive sheet 1. The preparation can be performed by uniformly mixing the carbon fibers 11, the thermally conductive filler, the binder resin, and various additives and volatile solvents as required by a known method.
[0080] <Process B>
[0081] Next, the prepared thermally conductive resin composition is formed into a block-shaped resin molded body 9 by extrusion molding or die molding.
[0082] The extrusion molding method and the die molding method are not particularly limited, and can be appropriately adopted from various known extrusion molding methods and die molding methods depending on the viscosity of the thermally conductive resin composition, the properties required of the thermally conductive sheet 1 , and the like.
[0083] When the thermally conductive resin composition is extruded through a die in the extrusion molding method or pressed into a die in the die molding method, the binder resin flows and some carbon fibers 11 are oriented along the flow direction, but most of them are randomly oriented.
[0084] It should be noted that when a slit is installed at the front end of the die, the carbon fibers 11 tend to be easily oriented in the central portion in the width direction of the extruded resin molded body 9. On the other hand, the peripheral portion in the width direction of the resin molded body 9 is affected by the slit wall, so that the carbon fibers 11 tend to be randomly oriented.
[0085] The size and shape of the resin molded body 9 can be determined according to the required size of the thermally conductive sheet 1. For example, a rectangular parallelepiped having a longitudinal dimension of 0.5 cm to 15 cm and a lateral dimension of 0.5 cm to 15 cm in cross section can be used. The length of the rectangular parallelepiped can be determined as required.
[0086] <Process C>
[0087] Next, the formed resin molded body 9 is sliced into sheets. Thus, the sheet body 7 is obtained. In the sheet body 7, the carbon fibers 11 are exposed from the surface of the sheet obtained by slicing (the slice surface). At this time, since both the resin molded body 9 and the carbon fibers 11 are cut, the insulating film 12 covering the carbon fibers 11 exposed from the sheet surface is removed (that is, the carbon fibers 11 exposed from the sheet surface are not covered by the insulating film 12). Therefore, the thermally conductive sheet 1 can maintain good thermal conductivity through the thickness direction.
[0088] There is no particular limitation on the slicing method, and it can be appropriately selected from the known slicing devices 13 (preferably ultrasonic cutters and planers) according to the size and mechanical strength of the resin molded body 9. As for the slicing direction of the resin molded body 9, when the molding method is an extrusion molding method, there is a situation where the slicing direction of the resin molded body 9 is oriented in the extrusion direction, so the slicing direction of the resin molded body 9 is 60 to 120 degrees relative to the extrusion direction, and more preferably 70 to 100 degrees. The direction of 90 degrees (vertical) is particularly preferred.
[0089] The thickness of the slice is not particularly limited and can be appropriately selected depending on the intended use of the thermally conductive sheet 1 and the like.
[0090] <Process D>
[0091] Next, the carbon fibers 11 exposed from the surface of the sheet body 7 are coated with a binder resin component. Examples of this method include the following method.
[0092] (1) By pressing the sheet body 7 , the surface of the sheet body 7 and the carbon fibers 11 exposed from the surface of the sheet body 7 are covered with the uncured component 8 of the binder resin that has seeped out from the sheet body 7 .
[0093] (2) By leaving the sheet body 7 in place, the surface of the sheet body 7 and the carbon fibers 11 exposed from the surface of the sheet body 7 are covered with the uncured component 8 of the binder resin that seeps out from the sheet body 7 .
[0094] First, the above-mentioned method (1) will be described.
[0095] The sliced surface of the obtained sheet body 7 is pressed. As a pressing method, a pair of pressing devices consisting of a flat plate and a pressing head with a flat surface can be used. Alternatively, pressing can be performed using pinch rollers.
[0096] Depending on the pressing conditions, the shape of the surface of the thermally conductive sheet that can be obtained varies.
[0097] Next, the above method (2) will be described.
[0098] The obtained sheet body 7 is left to stand. Depending on the standing time, the surface shape of the heat conductive sheet obtained varies.
[0099] For example, if it is placed for a short time, Figure 6 As shown, a thermally conductive sheet having protrusions on the surface derived from the carbon fibers 11 exposed from the surface of the sheet body 7 can be obtained.
[0100] On the other hand, if it is left for a long time, Figure 5 As shown, a thermally conductive sheet with a smooth surface can be obtained.
[0101] As a result, the uncured component 8 of the binder resin seeps out from the sheet body 7, and the surface of the sheet body 7 is coated with the uncured component 8 to obtain the thermally conductive sheet 1 (see Figure 3B ). In the thermally conductive sheet 1, the carbon fibers 11 exposed from the surface of the slice (the carbon fibers 11 not covered with the insulating film) are covered with the uncured component 8 of the binder resin. Therefore, the thermally conductive sheet 1 can ensure electrical insulation, and in the case of contact with the circuit around the semiconductor element, or in the case of a defect in the thermally conductive sheet 1 and falling onto the circuit, it is possible to prevent the failure of the electronic equipment due to a short circuit.
[0102] In addition, the thermally conductive sheet 1 exhibits slight tackiness (adhesiveness) on the sheet surface. Therefore, the thermally conductive sheet 1 can improve the conformability and adhesion to the surfaces of the electronic component 3 and the heat spreader 2, and can reduce thermal resistance.
[0103] Furthermore, since the surface of the sheet body 7 is coated with the uncured component 8 of the adhesive resin, the surface exhibits slight adhesiveness, thereby making it possible to adhere the thermally conductive sheet 1 to the main surface 2a of the heat spreader 2 or to temporarily fix it to the upper surface 3a of the electronic component 3. Therefore, the thermally conductive sheet 1 does not need to use an additional adhesive, and can achieve labor-saving and cost-reduction in the manufacturing process.
[0104] Furthermore, even if the thermally conductive sheet 1 loses slight surface adhesiveness during handling, if pressed, the uncured component 8 of the adhesive resin will seep out from the sheet body 7 again, and the surface will be covered with the uncured component 8. Therefore, even if the thermally conductive sheet 1 is deviated from the bonding position to the heat spreader 2 or the temporary fixing position to the electronic component 3, it can be repaired.
[0105] In addition, regarding the thermally conductive sheet 1, the uncured component 8 of the binder resin seeps out from the entire surface of the sheet body 7, and covers not only the surface and back surface of the sheet body 7 but also the side surfaces. Since the uncured component 8 of the binder resin has insulating properties, the thermally conductive sheet 1 imparts insulating properties to the side surfaces. Therefore, even if the thermally conductive sheet 1 bulges out from the periphery sandwiched between the electronic component 3 and the heat spreader 2 and contacts the conductive component disposed in the periphery, the semiconductor element, the heat sink, and the conductive component can be prevented from short-circuiting via the thermally conductive sheet 1.
[0106] The thermally conductive sheet 1 is compressed in the thickness direction by being pressed, and the frequency of contact between the carbon fibers 11 and the thermally conductive filler can be increased, thereby reducing the thermal resistance of the thermally conductive sheet 1. In addition, the surface of the thermally conductive sheet 1 is smoothed by being pressed.
[0107] If the pressure during pressing is too low, the thermal resistance tends to remain unchanged compared to the case of no pressing, while if it is too high, the sheet tends to stretch. Therefore, the pressure is preferably 0.0098 MPa to 9.8 MPa, and more preferably 0.049 MPa to 9.3 MPa.
[0108] In addition, regarding the thermal conductive sheet 1, as Figure 7 As shown, a spacer 10 is disposed on the placement surface facing the pressing head, and the sheet body 7 is pressed, so that the sheet body 7 can be formed to a predetermined sheet thickness according to the height of the spacer 10 .
[0109] When the thermally conductive sheet 1 is pressed, the uncured component 8 of the binder resin in the sheet body 7 seeps out and covers the entire surface of the sheet, and then the seepage stops. The pressing time can be appropriately set to a time sufficient for the uncured component 8 of the binder resin to seep out and cover the entire surface of the sheet body 7, depending on the mixing ratio of the binder resin component and the curing agent component in the binder resin, the pressing pressure, the sheet area, etc.
[0110] In addition, in the pressing process, in order to further promote the effect of the seepage of the uncured component 8 of the binder resin and the coating of the surface of the sheet body 7, a pressing head with a built-in heater can be used to perform the pressing process while heating. In order to improve such an effect, the heating temperature is preferably above the glass transition temperature of the binder resin. In this way, the pressing time can be shortened.
[0111] Example
[0112] Next, an example of the present invention will be described. In this example, the ratio of the binder component to the curing agent component of the thermally conductive resin composition and the presence or absence of insulation coating of the carbon fiber by the insulating film are changed to form a sample of the thermally conductive sheet. For each sample, the presence or absence of micro-adhesion, Shore OO hardness, compressive stress [N], initial thickness of the sheet [mm], thermal resistance (K·cm 2 / W), volume resistivity [Ω·cm].
[0113] [Production Example 1: Insulation Coating Treatment of Carbon Fiber]
[0114] The insulating coating on the carbon fibers used in the respective Examples was formed by the following method.
[0115] Put the first compound [300g of pitch-based carbon fiber (thermal conductive fiber: manufactured by Nippon Graphite Fiber Co., Ltd.) with an average fiber length of 100μm and an average fiber diameter of 9μm, 600g of tetraethoxysilane, and 2700g of ethanol] into a resin container (PE) and mix them using a stirring blade. It takes 5 minutes to add the second compound (1050g of 10% by mass ammonia water). The moment when the second compound is added is taken as 0 minutes, and stirring is performed for 3 hours. After the stirring is completed, use a vacuum pump for suction filtration, transfer the recovered sample to a beaker, wash it with water and ethanol, and filter it again to recover the sample. Dry the recovered sample at 100°C for 2 hours and calcine it at 200°C for 8 hours to obtain coated carbon fiber.
[0116] By measuring the cross section using TEM, a film mainly composed of SiO2 with an average thickness of 77nm was observed.
[0117] [Production Example 2: Insulation Coating Treatment of Carbon Fiber]
[0118] The insulating coating treatment of carbon fibers was performed in the same manner as in Production Example 1, except that the pitch-based carbon fibers in Production Example 1 were replaced with the following pitch-based carbon fibers, thereby obtaining coated carbon fibers.
[0119] · Pitch-based carbon fiber (thermal conductive fiber, average fiber length 150 μm, average fiber diameter 9 μm, manufactured by Nippon Graphite Fiber Co., Ltd.)
[0120] By measuring the cross section using TEM, a film mainly composed of SiO2 with an average thickness of 55nm was observed.
[0121] [Production Example 3: Insulation Coating Treatment of Carbon Fiber]
[0122] The insulating coating treatment of carbon fibers was performed in the same manner as in Production Example 1, except that the pitch-based carbon fibers in Production Example 1 were replaced with the following pitch-based carbon fibers, thereby obtaining coated carbon fibers.
[0123] · Pitch-based carbon fiber (thermal conductive fiber, average fiber length 90 μm, average fiber diameter 9 μm, manufactured by Nippon Graphite Fiber Co., Ltd.)
[0124] By measuring the cross section using TEM, a film mainly composed of SiO2 with an average thickness of 95nm was observed.
[0125] [Production Example 4: Insulation Coating Treatment of Carbon Fiber]
[0126] The insulating coating treatment of carbon fibers was performed in the same manner as in Production Example 1, except that the pitch-based carbon fibers in Production Example 1 were replaced with the following pitch-based carbon fibers, thereby obtaining coated carbon fibers.
[0127] · Pitch-based carbon fiber (thermal conductive fiber, average fiber length 110 μm, average fiber diameter 9 μm, manufactured by Nippon Graphite Fiber Co., Ltd.)
[0128] By measuring the cross section using TEM, a film mainly composed of SiO2 with an average thickness of 65nm was observed.
[0129] It should be noted that in Manufacturing Examples 1 to 4, the same processing conditions were used except for changing the average fiber length of the pitch-based carbon fibers. Even under the same processing conditions, the thickness of the formed film changes by changing the average fiber length of the pitch-based carbon fibers. Specifically, the longer the average fiber length of the carbon fibers, the thinner the thickness of the formed film becomes. It should be noted that the average fiber length of the carbon fibers is one of the factors that change the thickness of the coating.
[0130] [Determination of Shore OO hardness]
[0131] The Shore OO hardness of each thermally conductive sheet sample according to Examples 1 to 16 and Comparative Examples 1 to 6 was measured by the measurement method of ASTM-D2240.
[0132] [Measurement of compressive stress]
[0133] The thermally conductive sheets of Examples 1 to 16 and Comparative Examples 1 to 6 after the sheet body was pressed were measured for maximum compressive stress at a compression rate of 25.4 mm / min and 40% compression using a tension compression tester (TENSILON RTG1225, manufactured by A&D Corporation).
[0134] [Determination of thermal resistance]
[0135] In addition, the thermally conductive sheet samples according to Examples 1 to 16 and Comparative Examples 1 to 6 were subjected to a test under a load of 1.0 kgf / cm 2 The thermal resistance value is measured within the range of
[0136] [Measurement of volume resistivity]
[0137] In addition, the volume resistivity of each thermally conductive sheet sample according to Examples 1 to 16 and Comparative Examples 1 to 6 was measured by a method in accordance with JIS K-6911 using Hiresta (MCP-HT800) manufactured by Mitsubishi Chemical Analytech and a URS probe. The applied voltage was 100 V in Examples 1 to 16, 1 V in Comparative Examples 1 to 4, and 100 V in Comparative Examples 5 to 6.
[0138] In addition, in Comparative Examples 1 to 4, the applied voltage was set to 1 V because, unlike the Example and Comparative Examples 5 to 6, the measurement can be performed even with a low applied voltage.
[0139] [Example 1]
[0140] In Example 1, 20 vol% of alumina particles (thermal conductive particles: manufactured by Denki Kagaku Kogyo Co., Ltd., with an average particle size of 4 μm) coupled with a silane coupling agent, 22 vol% of coated carbon fibers (average fiber length of 100 μm, average fiber diameter of 9 μm) obtained in Production Example 1, and 24 vol% of aluminum nitride (thermal conductive particles: manufactured by Tokuyama Co., Ltd., with an average particle size of 1 μm) coupled with a silane coupling agent were dispersed in a two-component addition reaction type liquid silicone resin to prepare a silicone resin composition (thermal conductive resin composition).
[0141] The two-component addition reaction type liquid silicone resin is a mixture of 50% by mass of polysiloxane liquid A and 50% by mass of polysiloxane liquid B. It should be noted that the polysiloxane liquid A and the polysiloxane liquid B used in the following examples and comparative examples are the same as the above-mentioned polysiloxane liquid A and the above-mentioned polysiloxane liquid B, respectively.
[0142] The obtained silicone resin composition is extruded into a rectangular hollow mold (30 mm × 30 mm) with a PET film subjected to a peeling treatment attached to the inner wall to form a polysiloxane molded body. The obtained polysiloxane molded body is cured in an oven at 100°C for 6 hours to prepare a polysiloxane cured product. The obtained polysiloxane cured product is cut with an ultrasonic cutter to obtain a molded body sheet with a thickness of about 2 mm. The slicing speed of the ultrasonic cutter is set to 50 mm per second. In addition, regarding the ultrasonic vibration imparted to the ultrasonic cutter, the oscillation frequency is set to 20.5 kHz and the amplitude is set to 60 μm.
[0143] The obtained molded sheet was sandwiched between release-treated PET films, and then pressed with a 1.97 mm thick spacer to obtain a thermally conductive sheet sample whose surface was covered with uncured components of the binder resin. The pressing conditions were set at 80° C. and 1 MPa for 3 minutes.
[0144] The thickness of the insulating film covering the carbon fibers was 77 nm.
[0145] Regarding the thermal conductive sheet sample, the Shore OO hardness is 61, the initial thickness of the sheet is 1.998 mm, and the compressive stress is 900N.
[0146] It is slightly sticky on the surface of the sheet.
[0147] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 1 is 1.00 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 2.3×10 10 [Ω·cm].
[0148] [Example 2]
[0149] In Example 2, a thermally conductive sheet sample was prepared under the same conditions as in Example 1 except that a mixture of 55% by mass of polysiloxane A liquid and 45% by mass of polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin.
[0150] The thickness of the insulating film covering the carbon fibers was 77 nm.
[0151] Regarding the thermal conductive sheet sample, the Shore OO hardness is 55, the initial thickness of the sheet is 2.031 mm, and the compressive stress is 700N.
[0152] It is slightly sticky on the surface of the sheet.
[0153] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 2 is 0.95 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 2.7×10 10 [Ω·cm].
[0154] [Example 3]
[0155] In Example 3, a thermally conductive sheet sample was prepared under the same conditions as in Example 1 except that a mixture of 60 mass % of polysiloxane A liquid and 40 mass % of polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin.
[0156] The thickness of the insulating film covering the carbon fibers was 77 nm.
[0157] Regarding the thermal conductive sheet sample, the Shore OO hardness is 50, the initial thickness of the sheet is 2.005 mm, and the compressive stress is 450N.
[0158] It is slightly sticky on the surface of the sheet.
[0159] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 3 was 0.92 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 3.6×10 10 [Ω·cm].
[0160] [Example 4]
[0161] In Example 4, a thermally conductive sheet sample was prepared under the same conditions as in Example 1 except that a mixture of 65 mass % of polysiloxane A liquid and 35 mass % of polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin.
[0162] The thickness of the insulating film covering the carbon fibers was 77 nm.
[0163] Regarding the thermal conductive sheet sample, the Shore OO hardness is 42, the initial thickness of the sheet is 1.982 mm, and the compressive stress is 300N.
[0164] It is slightly sticky on the surface of the sheet.
[0165] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 4 is 0.94 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 4.4×10 10 [Ω·cm].
[0166] [Example 5]
[0167] In Example 5, a thermally conductive sheet sample was prepared under the same conditions as in Example 1, except that the coated carbon fibers (average fiber length: 150 μm) obtained in Production Example 2 were used as carbon fibers.
[0168] The thickness of the insulating film covering the carbon fibers was 55 nm.
[0169] Regarding the thermal conductive sheet sample, the Shore OO hardness is 70, the initial thickness of the sheet is 2.000 mm, and the compressive stress is 950N.
[0170] It is slightly sticky on the surface of the sheet.
[0171] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 5 was 0.91 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 3.6×10 9 [Ω·cm].
[0172] [Example 6]
[0173] In Example 6, a thermally conductive sheet sample was prepared under the same conditions as in Example 2, except that the coated carbon fibers (average fiber length: 150 μm) obtained in Production Example 2 were used as carbon fibers.
[0174] The thickness of the insulating film covering the carbon fibers was 55 nm.
[0175] Regarding the thermal conductive sheet sample, the Shore OO hardness is 58, the initial thickness of the sheet is 2.009 mm, and the compressive stress is 800N.
[0176] It is slightly sticky on the surface of the sheet.
[0177] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 6 is 0.88 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 4.7×10 9 [Ω·cm].
[0178] [Example 7]
[0179] In Example 7, a thermally conductive sheet sample was prepared under the same conditions as in Example 3, except that the coated carbon fibers (average fiber length: 150 μm) obtained in Production Example 2 were used as carbon fibers.
[0180] The thickness of the insulating film covering the carbon fibers was 55 nm.
[0181] Regarding the thermal conductive sheet sample, the Shore OO hardness is 57, the initial thickness of the sheet is 1.991 mm, and the compressive stress is 550N.
[0182] It is slightly sticky on the surface of the sheet.
[0183] In addition, regarding the thermally conductive sheet sample according to Example 7, the thermal resistance is 0.86 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 6.7×10 9 [Ω·cm].
[0184] [Example 8]
[0185] In Example 8, a thermally conductive sheet sample was prepared under the same conditions as in Example 4, except that the coated carbon fibers (average fiber length: 150 μm) obtained in Production Example 2 were used as carbon fibers.
[0186] The thickness of the insulating film covering the carbon fibers was 55 nm.
[0187] Regarding the thermal conductive sheet sample, the Shore OO hardness is 50, the initial thickness of the sheet is 2.016 mm, and the compressive stress is 350N.
[0188] It is slightly sticky on the surface of the sheet.
[0189] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 8 was 0.88 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100V is 8.2×10 9 [Ω·cm].
[0190] [Example 9]
[0191] In Example 9, 43 vol% of alumina particles (thermal conductive particles: manufactured by Denki Kagaku Kogyo Co., Ltd., with an average particle size of 4 μm) coupled with a silane coupling agent and 23 vol% of coated carbon fibers (average fiber length of 90 μm, average fiber diameter of 9 μm) obtained in Manufacturing Example 3 were dispersed in a two-component addition reaction type liquid silicone resin to prepare a silicone resin composition (thermal conductive resin composition).
[0192] The two-component addition reaction type liquid silicone resin is a mixture of 50% by mass of polysiloxane A liquid and 50% by mass of polysiloxane B liquid.
[0193] The obtained silicone resin composition is extruded into a rectangular hollow mold (30 mm × 30 mm) with a PET film subjected to a peeling treatment attached to the inner wall to form a polysiloxane molded body. The obtained polysiloxane molded body is cured in an oven at 100°C for 6 hours to prepare a polysiloxane cured product. The obtained polysiloxane cured product is cut with an ultrasonic cutter to obtain a molded body sheet with a thickness of about 2 mm. The slicing speed of the ultrasonic cutter is set to 50 mm per second. In addition, regarding the ultrasonic vibration imparted to the ultrasonic cutter, the oscillation frequency is set to 20.5 kHz and the amplitude is set to 60 μm.
[0194] The obtained molded sheet was sandwiched between release-treated PET films, and then pressed with a spacer to obtain a thermally conductive sheet sample whose surface was covered with uncured components of the binder resin. The pressing conditions were set at 80° C. and 1 MPa for 3 minutes.
[0195] The thickness of the insulating film covering the carbon fibers was 95 nm.
[0196] Regarding the thermal conductive sheet sample, the Shore OO hardness is 59, the initial thickness of the sheet is 2.017 mm, and the compressive stress is 900N.
[0197] It is slightly sticky on the surface of the sheet.
[0198] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 9 was 1.89 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100V is 1.2×10 10 [Ω·cm].
[0199] [Example 10]
[0200] In Example 10, a thermally conductive sheet sample was prepared under the same conditions as in Example 9 except that a mixture of 55 mass % of polysiloxane A liquid and 45 mass % of polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin.
[0201] The thickness of the insulating film covering the carbon fibers was 95 nm.
[0202] Regarding the thermal conductive sheet sample, the Shore OO hardness is 53, the initial thickness of the sheet is 2.008 mm, and the compressive stress is 800N.
[0203] It is slightly sticky on the surface of the sheet.
[0204] In addition, regarding the thermally conductive sheet sample according to Example 10, the thermal resistance is 1.83 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 2.9×10 10 [Ω·cm].
[0205] [Example 11]
[0206] In Example 11, a thermally conductive sheet sample was prepared under the same conditions as in Example 9 except that a mixture of 60 mass % of polysiloxane A liquid and 40 mass % of polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin.
[0207] The thickness of the insulating film covering the carbon fibers was 95 nm.
[0208] Regarding the thermal conductive sheet sample, the Shore OO hardness is 51, the initial thickness of the sheet is 1.982 mm, and the compressive stress is 500N.
[0209] It is slightly sticky on the surface of the sheet.
[0210] In addition, the thermal resistance of the thermally conductive sheet sample according to Example 11 was 1.79 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 4.2×10 10 [Ω·cm].
[0211] [Example 12]
[0212] In Example 12, a thermally conductive sheet sample was prepared under the same conditions as in Example 9 except that a mixture of 65 mass % of polysiloxane A liquid and 35 mass % of polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin.
[0213] The thickness of the insulating film covering the carbon fibers was 95 nm.
[0214] Regarding the thermal conductive sheet sample, the Shore OO hardness is 45, the initial thickness of the sheet is 1.996 mm, and the compressive stress is 250N.
[0215] It is slightly sticky on the surface of the sheet.
[0216] In addition, regarding the thermally conductive sheet sample according to Example 12, the thermal resistance is 1.85 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 5.5×10 10 [Ω·cm].
[0217] [Example 13]
[0218] In Example 13, a molded body sheet was produced under the same conditions as in Example 3, except that the coated carbon fibers (average fiber length: 110 μm) obtained in Production Example 4 were used.
[0219] After the obtained molded body sheet was sandwiched with a PET film subjected to a peeling treatment, a spacer with a thickness of 1.97 mm was inserted and pressed to obtain a thermally conductive sheet sample whose sheet surface was covered with uncured components of the binder resin. The pressing conditions were set to 100°C, 1 MPa, and 30 seconds. By setting the temperature to a higher temperature and shortening the pressing time, the sheet surface reflected the shape of the thermally conductive filler and was covered with components that did not react on the surface.
[0220] The thickness of the insulating film covering the carbon fibers was 65 nm.
[0221] Regarding the thermal conductive sheet sample, the Shore OO hardness is 52, the initial thickness of the sheet is 2.011 mm, and the compressive stress is 500N.
[0222] It is slightly sticky on the surface of the sheet.
[0223] In addition, regarding the thermally conductive sheet sample according to Example 13, the thermal resistance is 0.85 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 8.9×10 9 [Ω·cm].
[0224] [Example 14]
[0225] In Example 14, a molded body sheet was produced under the same conditions as in Example 4, except that the coated carbon fibers (average fiber length: 110 μm) obtained in Production Example 4 were used.
[0226] After the obtained molded body sheet was sandwiched with a PET film subjected to a peeling treatment, a spacer with a thickness of 1.97 mm was inserted and pressed to obtain a thermally conductive sheet sample whose sheet surface was covered with uncured components of the binder resin. The pressing conditions were set to 100°C, 1 MPa, and 30 seconds. By setting the temperature to a higher temperature and shortening the pressing time, the sheet surface reflected the shape of the thermally conductive filler and was covered with components that did not react on the surface.
[0227] The thickness of the insulating film covering the carbon fibers was 65 nm.
[0228] Regarding the thermal conductive sheet sample, the Shore OO hardness is 48, the initial thickness of the sheet is 1.978 mm, and the compressive stress is 330 N.
[0229] It is slightly sticky on the surface of the sheet.
[0230] In addition, regarding the thermally conductive sheet sample according to Example 14, the thermal resistance is 0.84 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100V is 8.3×10 9 [Ω·cm].
[0231] [Example 15]
[0232] In Example 15, a molded body sheet was produced under the same conditions as in Example 3 except that the coated carbon fibers (average fiber length: 110 μm) obtained in Production Example 4 were used.
[0233] The obtained molded sheet was sandwiched between PET films subjected to a release treatment and left for one day without pressing, thereby obtaining a thermally conductive sheet sample whose surface was covered with uncured components of the binder resin, so that the sheet surface reflected the shape of the thermally conductive filler and was covered with components that did not react on the surface.
[0234] The thickness of the insulating film covering the carbon fibers was 65 nm.
[0235] Regarding the thermal conductive sheet sample, the Shore OO hardness is 50, the initial thickness of the sheet is 2.023 mm, and the compressive stress is 400N.
[0236] It is slightly sticky on the surface of the sheet.
[0237] In addition, regarding the thermally conductive sheet sample according to Example 15, the thermal resistance is 0.88 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100 V is 9.4×10 9 [Ω·cm].
[0238] [Example 16]
[0239] In Example 16, a molded body sheet was produced under the same conditions as in Example 3, except that the coated carbon fibers (average fiber length: 110 μm) obtained in Production Example 4 were used.
[0240] The obtained molded sheet was sandwiched between release-treated PET films and left for one week without pressing to obtain a thermally conductive sheet sample whose sheet surface was covered with uncured components of the binder resin. The sheet surface was covered with components that did not react with the surface of the thermally conductive sheet.
[0241] The thickness of the insulating film covering the carbon fibers was 65 nm.
[0242] Regarding the thermal conductive sheet sample, the Shore OO hardness is 49, the initial thickness of the sheet is 2.001 mm, and the compressive stress is 350N.
[0243] It is slightly sticky on the surface of the sheet.
[0244] In addition, regarding the thermally conductive sheet sample according to Example 16, the thermal resistance is 0.90 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100V is 1.2×10 10 [Ω·cm].
[0245] [Comparative Example 1]
[0246] In Comparative Example 1, a thermally conductive sheet sample was prepared under the same conditions as in Example 1 except that pitch-based carbon fibers (thermal conductive fibers: manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length 100 μm, average fiber diameter 9 μm) without insulation coating treatment were used.
[0247] The thermally conductive sheet sample according to Comparative Example 1 had a Shore OO hardness of 72, an initial thickness of the sheet of 2.010 mm, and a compressive stress of 1000 N.
[0248] It is slightly sticky on the surface of the sheet.
[0249] In addition, the thermal resistance of the thermally conductive sheet sample according to Comparative Example 1 was 0.88 [K·cm 2 / W], and the volume resistivity when the applied voltage is 1V is 3.4×10 4 [Ω·cm].
[0250] [Comparative Example 2]
[0251] In Comparative Example 2, a thermally conductive sheet sample was prepared under the same conditions as in Example 2 except that pitch-based carbon fibers (thermal conductive fibers: manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length 100 μm, average fiber diameter 9 μm) without insulation coating treatment were used.
[0252] The thermally conductive sheet sample according to Comparative Example 2 had a Shore OO hardness of 63, an initial thickness of the sheet of 1.99 mm, and a compressive stress of 900 N.
[0253] It is slightly sticky on the surface of the sheet.
[0254] In addition, the thermal resistance of the thermally conductive sheet sample according to Comparative Example 2 was 0.85 [K·cm 2 / W], and the volume resistivity when the applied voltage is 1V is 3.6×10 4 [Ω·cm].
[0255] [Comparative Example 3]
[0256] In Comparative Example 3, a thermally conductive sheet sample was prepared under the same conditions as in Example 3 except that pitch-based carbon fibers (thermal conductive fibers: manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length 100 μm, average fiber diameter 9 μm) without insulation coating treatment were used.
[0257] The thermally conductive sheet sample according to Comparative Example 3 had a Shore OO hardness of 59, an initial thickness of the sheet of 1.999 mm, and a compressive stress of 450 N.
[0258] It is slightly sticky on the surface of the sheet.
[0259] In addition, the thermal resistance of the thermally conductive sheet sample according to Comparative Example 3 was 0.84 [K·cm 2 / W], and the volume resistivity when the applied voltage is 1V is 3.9×10 4 [Ω·cm].
[0260] [Comparative Example 4]
[0261] In Comparative Example 4, a thermally conductive sheet sample was prepared under the same conditions as in Example 4 except that pitch carbon fibers (thermal conductive fibers: manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length 100 μm, average fiber diameter 9 μm) without insulation coating treatment were used.
[0262] The thermally conductive sheet sample according to Comparative Example 4 had a Shore OO hardness of 50, an initial thickness of the sheet of 2.005 mm, and a compressive stress of 300N.
[0263] It is slightly sticky on the surface of the sheet.
[0264] In addition, the thermal resistance of the thermally conductive sheet sample according to Comparative Example 4 was 0.87 [K·cm 2 / W], and the volume resistivity when the applied voltage is 1V is 4.7×10 4 [Ω·cm].
[0265] [Comparative Example 5]
[0266] In Comparative Example 5, a mixture of 50 mass % polysiloxane A liquid and 50 mass % polysiloxane B liquid, which is a two-component addition reaction type liquid silicone resin, was applied to the thermally conductive sheet obtained in Comparative Example 1 to prepare a thermally conductive sheet sample.
[0267] The thermally conductive sheet sample according to Comparative Example 5 had a Shore OO hardness of 75, an initial thickness of the sheet of 2.030 mm, and a compressive stress of 1050 N.
[0268] It is slightly sticky on the surface of the sheet.
[0269] In addition, the thermal resistance of the thermally conductive sheet sample according to Comparative Example 5 was 2.43 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100V is 1.0×10 12 [Ω·cm].
[0270] [Comparative Example 6]
[0271] In Comparative Example 6, a thermally conductive sheet sample was prepared under the same conditions as in Comparative Example 5, except that a mixture of 45 mass % polysiloxane A liquid and 55 mass % polysiloxane B liquid was used as the two-component addition reaction type liquid silicone resin to be applied.
[0272] The thermally conductive sheet sample according to Comparative Example 6 had a Shore OO hardness of 75, an initial thickness of the sheet of 2.015 mm, and a compressive stress of 1200 N.
[0273] There was no slight stickiness on the sheet surface.
[0274] In addition, the thermal resistance of the thermally conductive sheet sample according to Comparative Example 6 was 2.56 [K·cm 2 / W], and the volume resistivity at an applied voltage of 100V is 8.1×10 11 [Ω·cm].
[0275] [Evaluation of slight adhesiveness]
[0276] In addition, slight adhesion was evaluated for each thermally conductive sheet sample involved in Examples 1 to 16 and Comparative Examples 1 to 6. For the evaluation of slight adhesion, the polysiloxane cured products involved in Examples 1 to 16 and Comparative Examples 1 to 6 were sliced, the obtained molded body sheets were sandwiched with PET films that were not subjected to a release treatment, and a spacer with a thickness of 1.97 mm was inserted, and pressed at 80° C. and 2.45 MPa for 3 minutes, and then cooled to room temperature, thereby obtaining thermally conductive sheet samples for slight adhesion evaluation.
[0277] The end of the PET film of the thermal conductive sheet sample for evaluating the micro-adhesion was peeled off by hand, and after clamping the end with a testing machine, it was stretched at 90° at a speed of 50mm / mm, and the load was measured. The micro-adhesion (adhesiveness) was evaluated based on the peeling force (load). The peeling force of each sample was measured while maintaining a predetermined width. The evaluation was based on the following evaluation criteria.
[0278] [Evaluation criteria]
[0279] ◎(Optimum): When the peel force varies within the range of 0.05 to 0.25 (N / cm)
[0280] ○ (good): The peeling force varies within the range of 0.02 to 0.05 (N / cm), 0.20 to 0.30 (N / cm)
[0281] △ (Normal): When the peel force varies within the range of 0 to 0.04 (N / cm)
[0282] × (bad): A portion of the sheet where slight tackiness was not observed was observed.
[0283] [Table 1]
[0284] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Polysiloxane resin A liquid [%] 50 55 60 65 50 55 Polysiloxane resin B liquid [%] 50 45 40 35 50 45 Fiber length of carbon fiber [μm] 100 100 100 100 150 150 Insulation film thickness [nm] 77 77 77 77 55 55 Slightly sticky △ ○ ◎ ◎ △ ○ Shore 00 hardness 61 55 50 42 70 58 Compressive stress [N] 900 700 450 300 950 800 Initial thickness of sheet [mm] 1.998 2.031 2.005 1.982 2.000 2.009 <![CDATA[Thermal resistance [K·cm 2 / W]]]> 1.00 0.95 0.92 0.94 0.91 0.88 Volume resistivity [Ω·cm] <![CDATA[2.3×10 10 ]]> <![CDATA[2.7×10 10 ]]> <![CDATA[3.6×10 10 ]]> <![CDATA[4.4×10 10 ]]> <![CDATA[3.6×10 9 ]]> <![CDATA[4.7×10 9 ]]>
[0285] [Table 2]
[0286] Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Polysiloxane resin A liquid [%] 60 65 50 55 60 65 Polysiloxane resin B liquid [%] 40 35 50 45 40 35 Fiber length of carbon fiber [μm] 150 150 90 90 90 90 Insulation film thickness [nm] 55 55 95 95 95 95 Slightly sticky ◎ ◎ △ ○ ◎ ◎ Shore 00 hardness 57 50 59 53 51 45 Compressive stress [N] 550 350 900 800 500 250 Initial thickness of sheet [mm] 1.991 2.016 2.017 2.008 1.982 1.996 <![CDATA[Thermal resistance [K·cm 2 / W]]]> 0.86 0.88 1.89 1.83 1.79 1.85 Volume resistivity [Ω·cm] <![CDATA[6.7×10 9 ]]> <![CDATA[8.2×10 9 ]]> <![CDATA[1.2×101 0 ]]> <![CDATA[2.9×10 10 ]]> <![CDATA[4.2×10 10 ]]> <![CDATA[5.5×10 10 ]]>
[0287] [Table 3]
[0288] Embodiment 13 Embodiment 14 Embodiment 15 Example 16 Polysiloxane resin A liquid [%] 60 65 60 60 Polysiloxane resin B liquid [%] 40 35 40 40 Fiber length of carbon fiber [μm] 110 110 110 110 Insulation film thickness [nm] 65 65 65 65 Slightly sticky ◎ ◎ ◎ ◎ Shore 00 hardness 52 48 50 49 Compressive stress [N] 500 330 400 350 Initial thickness of sheet [mm] 2.011 1.978 2.023 2.001 <![CDATA[Thermal resistance [K·cm 2 / W]]]> 0.85 0.84 0.88 0.90 Volume resistivity [Ω·cm] <![CDATA[8.9×10 9 ]]> <![CDATA[8.3×10 9 ]]> <![CDATA[9.4×10 9 ]]> <![CDATA[1.2×10 10 ]]>
[0289] [Table 4]
[0290] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Polysiloxane resin A liquid [%] 50 55 60 65 50 45 Polysiloxane resin B liquid [%] 50 45 40 35 50 55 Fiber length of carbon fiber [μm] 100 100 100 100 100 100 Slightly sticky △ ○ ◎ ◎ △ × Shore 00 hardness 72 63 59 50 75 75 Compressive stress [N] 1000 900 450 300 1050 1200 Initial thickness of sheet [mm] 2.010 1.990 1.999 2.005 2.030 2.015 <![CDATA[Thermal resistance [K·cm 2 / W]]]> 0.88 0.85 0.84 0.87 2.43 2.56 Volume resistivity [Ω·cm] <![CDATA[3.4×10 4 ]]> <![CDATA[3.6×10 4 ]]> <![CDATA[3.9×10 4 ]]> <![CDATA[4.7×10 4 ]]> <![CDATA[1.0×10 12 ]]> <![CDATA[8.1×10 11 ]]>
[0291] As shown in Tables 1 to 4, the maximum thermal resistance of the thermally conductive sheet samples according to Examples 1 to 16 was 1.89 [K·cm 2 / W], and the minimum volume resistivity is 3.6×10 9 [Ω·cm], basically achieving both thermal conductivity and insulation. This is because the carbon fibers contained in the thermally conductive sheet sample are coated with an insulating film having a thickness of 50 nm or more and less than 100 nm. Therefore, the insulating film is formed according to the desired film thickness, which can have a good volume resistivity, and the generation of silica particles is suppressed, which can prevent the reduction of thermal conductivity. In addition, with respect to the thermally conductive sheet samples involved in Examples 1 to 16, regarding the carbon fibers exposed from the surface of the sheet, since the insulating film is cut during slicing, the carbon fibers are exposed, but are covered with the uncured components of the adhesive resin, so the thermal conductivity is not impaired, and the insulation to the surrounding components is provided.
[0292] It should be noted that in Examples 1 to 12 and 16, Figure 5 As shown in FIG. 13 , a thermally conductive sheet with a smooth surface was obtained. Figure 6 As shown, a thermally conductive sheet having protrusions on its surface derived from carbon fibers exposed from the surface of the sheet body was obtained.
[0293] On the other hand, since the thermally conductive sheet samples of Comparative Examples 1 to 4 used carbon fibers without an insulating film, although the thermal resistance was suppressed to a low level, the volume resistivity was low and the insulation was insufficient. In addition, since the thermally conductive sheet samples of Comparative Examples 5 and 6 were further coated with a binder resin, although the volume resistivity was high and the insulation was excellent, the carbon fibers were buried in the binder resin, and thus the thermal resistance became high.
[0294] It should be noted that, in the thermally conductive sheet sample involved in Comparative Example 6, the composition ratio of the polysiloxane A liquid in the applied silicone resin is low, which is 45%, and the uncured components remain insufficiently. Even if pressed, the entire surface of the sheet cannot be covered, and slight adhesion is not exhibited in a part. Therefore, in the thermally conductive sheet sample involved in Comparative Example 6, temporary fixation to the connection object cannot be performed at the position where slight adhesion is not exhibited, and the operability is poor. In addition, the thermally conductive sheet sample involved in Comparative Example 6 lacks flexibility, and has poor compliance and adhesion to the bonding object, and the thermal resistance increases.
[0295] Explanation of symbols
[0296] 1: thermal conductive sheet; 2: heat spreader; 2a main surface; 3: electronic component; 3a upper surface; 4: heat dissipating component; 5: heat sink; 6: wiring board; 7: sheet body; 8: uncured component; 9: resin molded body; 10: spacer; 11: carbon fiber; 12: insulating film; 13: slicing device.
Claims
1. A thermally conductive sheet having a sheet body formed by curing a thermally conductive resin composition, wherein the thermally conductive resin composition contains a binder resin and carbon fibers coated with an insulating film, The carbon fibers exposed from the cut surface of the sheet body are not covered by the insulating film but are covered by uncured components of the binder resin that have seeped out from the sheet body. The Shore OO hardness measured by the measurement method according to ASTM-D2240 is 70 or less. 2 . The thermally conductive sheet according to claim 1 , wherein the surface of the sheet has protrusions derived from the carbon fibers exposed from a cut surface of the sheet body.
3. The thermally conductive sheet according to claim 1 or 2, wherein the insulating film covering the carbon fibers is silicon oxide. The average thickness of the insulating film observed by cross-sectional TEM observation is 50 nm or more and less than 100 nm.
4. The thermally conductive sheet according to claim 1 or 2, having a thermal resistance of 0.84K·cm 2 / W~1.85K·cm 2 / W. The thermally conductive sheet according to claim 1 or 2, wherein the sheet body contains a thermally conductive filler. 6 . The thermally conductive sheet according to claim 1 , wherein a surface of the sheet body is coated with an uncured component of the binder resin.
7. A method for manufacturing a thermally conductive sheet, comprising the following steps: A step of molding a thermally conductive resin composition containing a binder resin and carbon fibers covered with an insulating film into a predetermined shape and curing the shape to obtain a molded body of the thermally conductive resin composition; The step of cutting the molded body into sheets to obtain a sheet body; and a step of coating the carbon fibers exposed from the cut surface of the sheet body with uncured components of the binder resin exuded from the sheet body, In the step of obtaining the sheet body, the insulating film covering the carbon fibers exposed from the cut surface of the sheet body is removed. The Shore OO hardness measured by the measurement method according to ASTM-D2240 is 70 or less.
8. The method for manufacturing a thermally conductive sheet according to claim 7, wherein the covering step is a step of covering the surface of the sheet body and the carbon fibers exposed from a cut surface of the sheet body with uncured components of the adhesive resin that seeps out from the sheet body by pressing the sheet body.
9. The method for manufacturing a thermally conductive sheet according to claim 7, wherein the covering step is a step of placing the sheet body and covering the surface of the sheet body and the carbon fibers exposed from the cut surface of the sheet body with uncured components of the adhesive resin that seeps out from the sheet body.
10. The method for producing a thermally conductive sheet according to any one of claims 7 to 9, comprising extruding and filling the thermally conductive resin composition in a hollow mold, and thermally curing the thermally conductive resin composition to obtain the molded body in which the carbon fibers are randomly oriented with respect to the extrusion direction.
11. A heat release component, comprising: A heat dissipator for dissipating heat generated by electronic components; and The thermally conductive sheet according to any one of claims 1 to 6, which is disposed on the heat spreader and sandwiched between the heat spreader and the electronic component.
12. A semiconductor device comprising: Semiconductor components; a heat dissipator for dissipating heat generated by the semiconductor element; and The thermally conductive sheet according to any one of claims 1 to 6, which is disposed on the heat spreader and sandwiched between the heat spreader and the semiconductor element. 13 . The semiconductor device according to claim 12 , comprising a heat sink, wherein the thermally conductive sheet according to claim 1 is sandwiched between the heat spreader and the heat sink.
Citation Information
Patent Citations
Thermally conductive sheet and method of producing the same
JP2012023335A
Heat conductive molded body and manufacturing method thereof and semiconductor device
EP1041627A2
Heat-conductive sheet
JP2000117898A